PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER-PLUS UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH SISWA KELAS XI JURUSAN TEKNIK GAMBAR BANGUNAN 3 SMK NEGERI 2 PEKANBARU - Zulhaida Zulhaida (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research describes the improvement of learning outcomes History of Indonesia students class XI BuildingMaterials Engineering Department 3 SMK Negeri 2 Pekanbaru with Classroom Action Research. Learningmodel used is cooperative learning type numbered head together-plus. This type is applied in the study ofhistory, which analyzes the impact of politics, culture, socio-economic, and education during the Japanesecolonial era in the life of the Indonesian nation today, in Basic Competence (3.6) in class XI subjects ofIndonesian history. Number of students are 28 people. Average score before using the numbered head togetherplus type is 75.75 (moderate category), with eight complete students (28.57%). The results showed that learningwith cooperative model type numbered head together plus have positive impact in improving student learningoutcomes. The increase was marked by the improvement of students' learning mastery of the cycle, that is, in thefirst cycle of students who completed totaling 12 people (42.88%), with an average score of 76.96 and in cycle IIcomplete students amounted to 26 people (92.86%) with an average value of 81.79.